Biotechnological production of fumaric acid: The effect of morphology of Rhizopus arrhizus NRRL 2582 - Papadaki, Aikaterini; Androutsopoulos, Nikolaos; Patsalou, Maria; Koutinas, Michalis; Kopsahelis, Nikolaos; De Castro, Aline Machado; Papanikolaou, Seraphim; Koutinas, Apostolis A. (My University, 2017)
Fumaric acid is a platform chemical with many applications in bio-based chemical and polymer production. Fungal cell morphology is an important factor that affects fumaric acid production via fermentation. In the present study, pellet and dispersed mycelia morphology of Rhizopus arrhizus NRRL 2582 was analysed using image analysis software and the impact on fumaric acid production was evaluated. Batch experiments were carried out in shake flasks using glucose as carbon source. The highest fumaric acid yield of 0.84 g/g total sugars was achieved in the case of dispersed mycelia with a final fumaric acid concentration of 19.7 g/L. The fumaric acid production was also evaluated using a nutrient rich feedstock obtained from soybean cake, as substitute of the commercial nitrogen sources. Solid state fermentation was performed in order to produce proteolytic enzymes, which were utilised for soybean cake hydrolysis. Batch fermentations were conducted using 50 g/L glucose and soybean cake hydrolysate achieving up to 33 g/L fumaric acid concentration. To the best of our knowledge the influence of R. arrhizus morphology on fumaric acid production has not been reported previously. The results indicated that dispersed clumps were more effective in fumaric acid production than pellets and renewable resources could be alternatively valorised for the biotechnological production of platform chemicals.
Keywords: Aspergillus oryzae; Biorefinery; Enzymatic hydrolysis; Fumaric acid; Fungal morphology; Image analysis; Rhizopus; Soybean cake